Long-distance trade and consumption of mollusks in the Byzantine and Early Islamic periods in the Negev Desert. (June 2021) - Ktalav, Inbar; Tepper, Yotam; Gambash, Gil; Lehnig, Sina; Bar-Oz, Guy
Highlights: A large number of edible shellfish were uncovered at Byzantine sites in the Negev Desert, Israel. The shellfish originated from three distinct habitats: Red Sea, Mediterranean Sea, and Nile River. Taphonomic analysis revealed that some of the shellfish had been collected live and others as empty shells gathered on the shore. Shellfish remains contribute to the evaluation of practices of transportation and long-distance trade in edible aquatic products. Abstract: Recent archaeological excavations in the Negev desert in the southern Levant have yielded a variety of mollusk shells originating from the Mediterranean Sea, the Nile River, and the Red Sea, uncovered in the trash mounds and settlements of Byzantine and Early Islamic sites. These remains indicate that aquatic products were among the merchandised comestibles transported across long distances. Three shellfish taxa manifest such transportation: (1) the small clam, Donax trunculus, commonly found in the exposed sandy wash zones of the Eastern Mediterranean coast; (2) the large freshwater mussel, Chambardia rubens, whose habitat stretches from the Nile River to western Africa; and (3) the large conch, Lambis truncata, commonly found in the shallow waters of the Red Sea. The breakage and abrasion patterns of the shell fragments of these three species suggest that they were collected as live specimens and not as empty shells washed ashore. The other taxa, however, were mostly collected as empty shells to be used, for example, as ornaments.